Plasmodium knowlesi reinfection in human - Lau, Y.L.; Tan, L.H.; Chin, L.C.; Fong, M.Y.; Noraishah, M.A.; Rohela, M. (2011)
To the Editor: In 2004, a large number of patients infected with Plasmodium knowlesi (simian malarial species) were reported in Sarawak, Malaysia (1). P. knowlesi infection was also reported in Peninsular Malaysia (2). Here we report a case of human P. knowlesi reinfection. Phylogenetic sequence analysis shows that the first and second infections were caused by different strains of P. knowlesi.